Merdeka Curriculum Learning Strategy in Effort Building Student Potential - Sulaiman W; Muhammad Nur; Sulaiman Ismail (International Journal of Educational Narratives, 2024)
Background. Learning strategies in the independent curriculum must be optimized for teachers as the spearhead in advancing mutually beneficial education. If this is not realized, then the government's hopes of overcoming the weaknesses of Indonesian education will not be realized. This benchmark is the reference for researchers to describe how the Merdeka Curriculum learning strategies are used to build student potential. Purpose. This qualitative research describes how the Merdeka Curriculum learning strategies build student potential. Method. This study refers to "Literature Studies," where books and research results are the main sources of data as material for describing good Merdeka Curriculum learning strategies. Results. In the Merdeka Curriculum, appropriate learning strategies to achieve goals can be realized through project-based, collaborative, technology-based, problem-based, and experience-based learning. Conclusion. If this project-based, collaborative, technology-based, problem-based, and experience-based learning strategy can be realized well, students can develop interests, talents, and skills that match their potential. Thus, applying these strategies in the Merdeka Curriculum can provide meaningful and relevant learning experiences for students.